Impact of Primary Education on Economic Development: Exploring the long-term impact of primary education on GDP in India (Journal of Advances and Scholarly Researches in Allied Education, 2014)
The objective of this studyis to explore the long-term impact of primary education on GDP. By using theannual data, the present study tries to explore the impact of education on GDPin India through time series tools. Empirical results suggest that primaryeducation have positive long-term impact on GDP of the nation. In other words,primary education is playing an important role in the growth of GDP of thenation during the last decade. The above findings, thus, suggest that if Indiawants to enhance GDP (reduce poverty and enhance economic development), itshould take some special measures to increase for primary education and deepenthe ongoing reform process through a consensus among all political parties.There is not much study on poverty in India especially exploring the long-termrelationship among primary education and its impact on GDP of the nation. Thus, the present study hasits own originality and will add value to policy makers.